1983
DOI: 10.1038/clpt.1983.251
|View full text |Cite
|
Sign up to set email alerts
|

Ampicillin and cephalexin in renal insufficiency

Abstract: We analyzed the relationship between functional damage and transport processes in the kidney in patients with glomerulonephritis and renal failure by a new analytic method. In renal failure patients, there was substantial diminution of maximum transport of secretion in renal tubules. This reduction affected the urinary excretion of ampicillin and cephalexin substantially because both drugs depend on active renal tubular secretion. Our results indicate that dosage adjustment based on creatinine clearance is not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

1988
1988
1998
1998

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 0 publications
1
20
0
Order By: Relevance
“…Tmax CLus, mt-K, M + CI (11) where Tmax is the transport maximum (mass. time-1), CI is the concentration of unbound drug in the vicinity of tubular secretion sites, and K'M is the Michaelis constant (mass.…”
Section: The Definition Of Intrinsic Tubular Secretion Clearance and mentioning
confidence: 99%
See 1 more Smart Citation
“…Tmax CLus, mt-K, M + CI (11) where Tmax is the transport maximum (mass. time-1), CI is the concentration of unbound drug in the vicinity of tubular secretion sites, and K'M is the Michaelis constant (mass.…”
Section: The Definition Of Intrinsic Tubular Secretion Clearance and mentioning
confidence: 99%
“…Experimental [8] and clinical [4,9] data demonstrate that the renal clearance of a drug will approach zero in kidney failure, even if the drug is excreted by filtration and also by tubular secretion, which lends support to this hypothesis. On the other hand, there is some evidence that dosing adjustments based on simple proportionality of renal drug clearance to GFR may not be entirely adequate for certain drugs secreted in the tubules due to nonparallel behaviour of GFR and tubular secretion [10,11].…”
mentioning
confidence: 99%
“…Creatinine, being cleared mainly by glomerular filtration, provides direct information only on the capacity for glomerular filtration but in many circumstances may correlate poorly with the other func tions o f the nephron, namely, tubular secretion and reab sorption. Because o f this limitation, several compounds have been investigated for their ability to measure the secretory capacity o f the kidney; these include p-aminohippuric acid [2], phenolsulphonephthalein [3] and tetraethylammonium [4], However, these substances are all ex ogenous and therefore need to be infused. In addition, for organic anions such as p-aminohippurate, other anions that can accumulate in uraemic blood may inhibit the renal tubular secretion o f the marker [5].…”
Section: Introductionmentioning
confidence: 99%
“…Marre et al [11] and Toyoguchi and Nakagawa [12] reported that imipenem-cilastatin, flomoxef or fosfomycin may decrease the nephrotoxicity of VCM by inhibiting into the kidney. However, the interactions among LVFX and VCM are not clear [11][12][13][14]. Therefore, we studied the changes in the pharmacokinetics of LVFX and VCM when both agents were administered concomitantly to rats.…”
Section: Introductionmentioning
confidence: 99%